(untitled) (Indian Journal of Child Health, 2022)
Vitamin D3 (cholecalciferol) is a fat-soluble vitamin that is essential for the skeletal health. Here, we discuss a case of a child from an upper middle-class family who presented with gradually progressive proximal myopathy and gait abnormality over 3 years. She was found to have severe vitamin D deficiency, resulting in proximal myopathy and pubic arch fractures with slipped capital femoral epiphysis, leading to the gait abnormality. In our country in spite of ample sunlight, vitamin D3 deficiency is rampant. The patient highlights the need of considering vitamin D deficiency as one of the differentials in myopathy and gait abnormalities in children.